2020
DOI: 10.1136/rmdopen-2019-001145
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility criteria for biologic disease-modifying antirheumatic drugs in axial spondyloarthritis: going beyond BASDAI

Abstract: ObjectivesTo compare definitions of high disease activity of the Ankylosing Spondylitis Disease Activity Score (ASDAS) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) in selecting patients for treatment with biologic disease-modifying antirheumatic drugs (bDMARDs).MethodsPatients from Rheumatic Diseases Portuguese Register (Reuma.pt) with a clinical diagnosis of axial spondyloarthritis (axSpA) were included. Four subgroups (cross-tabulation between ASDAS (≥2.1) and BASDAI (≥4) definitions of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Consistent with our results, one previous study indicated that 36.9% (210/568 patients) of patients with low BASDAI scores (< 4) had high disease activity as measured by the ASDAS-CRP (≥ 2.1) [11]. Moreover, even higher percentages of patients having high ASDAS-CRP (≥ 2.1) among those having low BASDA score (< 4) were shown in two other studies; 62.1% (64/103 patients) and 65.8% (48/73 patients) [12,13].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistent with our results, one previous study indicated that 36.9% (210/568 patients) of patients with low BASDAI scores (< 4) had high disease activity as measured by the ASDAS-CRP (≥ 2.1) [11]. Moreover, even higher percentages of patients having high ASDAS-CRP (≥ 2.1) among those having low BASDA score (< 4) were shown in two other studies; 62.1% (64/103 patients) and 65.8% (48/73 patients) [12,13].…”
Section: Discussionmentioning
confidence: 79%
“…One previous study investigating eligibility criteria for initiation of anti-TNF treatment in AS patients showed that an ASDAS-CRP result ≥ 2.1 is associated with a greater likelihood of improvement than a high BASDAI score (≥ 4), but the patients who had both ASDAS-CRP ≥ 2.1 and BASDAI ≥ 4 showed the greatest improvement [12]. Similarly, from another prospective cohort study, applying the ASDAS definition of high disease activity leads to more axial SpA patients being selected to start anti-TNF treatment and these 'captured' patients have a greater likelihood of known predictors of good response to anti-TNF than traditional BASDAI definition (≥ 4) [13]. One study including patients with AS and undifferentiated SpA treated with etanercept or infliximab revealed that the discriminatory ability of the ASDAS outperformed that of the BASDAI, patient global score, ESR, CRP, or acute inflammation score as assessed by MRI [19].…”
Section: Discussionmentioning
confidence: 96%
“…Finally, while not a primary aim of this study but because Australian data are lacking, we used these two datasets to estimate the population prevalence of AS. Based on the assumption that the 1925 AS patients that used a TNFi in 2020 represent 60% of all AS patients [16,17] in WA, the estimated point prevalence for AS was 0.29% in 2020. This figure agreed with the 0.28% period prevalence rate of AS amongst all hospital admissions in WA over 20 years (Suppl Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the lack of efficacy of traditional disease-modifying drugs in AS [ 11 ], the rapid uptake of TNFi following its approval for AS in Australia is not unexpected and in line with early expectations that, depending on national health care systems, 38–78% of AS patients attending rheumatology clinics in Europe would be initiated on TNFi therapy [ 18 ]. Current data suggest that at least 60% of AS patients will be initiating TNFi when following BASDAI-based guidelines, which are also in use in Australia [ 17 ]. This number can be expected to increase in the future as AS patients with BASDAI scores < 4 also have significant reductions in disease activity with TNFi [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation